${{\sqrt 2 } \over {\sqrt {(2 + \sqrt 3 )} - \sqrt {(2 - \sqrt 3 } )}} = $

  • A

    $0$

  • B

    $1$

  • C

    $\sqrt 2 $

  • D

    $1/\sqrt 2 $

Similar Questions

If $x = {2^{1/3}} - {2^{ - 1/3}},$ then $2{x^3} + 6x = $

If ${a^{1/x}} = {b^{1/y}} = {c^{1/z}}$ and ${b^2} = ac$ then $x + z = $

If $a = \sqrt {(21)} - \sqrt {(20)} $ and $b = \sqrt {(18)} - \sqrt {(17),}  $ then

If ${a^x} = {b^y} = {(ab)^{xy}},$ then $x + y = $

If ${x^{x\root 3 \of x }} = {(x\,.\,\root 3 \of x )^x},$ then $x =$